Convergence around concepts of actual board effectiveness in hard and soft law. (2nd January 2015) - Stewart, Abigail; McNulty, Terry
Abstract : This article examines the development of "soft law", the comply or explain corporate governance regulation of the listed UK plc, over the decade from 2003, to revisions in October 2014. We will also consider the "hard law" of governance regulation, as it has developed through the codification of directors' duties under the Companies Act 2006 (CA 2006). Our particular focus is on provisions in both soft and hard law that have sought to promote and enhance board effectiveness, and in particular, how that can be achieved through the work and function of the non-executive director. The article seeks to create a behavioural perspective which we hope complements the jurisprudential analysis of these provisions. The article highlights the behavioural and relational emphasis within these legislative and regulatory provisions, as a significant feature of the ongoing corporate governance reform agenda.